INDONESIAN JUDICIAL POWER POST AMENDMENT - Nasution, Krisnadi (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Post the amendment of the Republic of Indonesia constitution, judicial authority in Indonesia underwent a fundamental change. The amendment was made based on the mandate contained in the 1945 Constitution post the amendment. Through normative juridical studies, an analysis of these changes will be carried out. The method of approach is based on statutory regulations and conceptually, as well as comprehensive. Post the amendment of the Republic of Indonesia Constitution, in the beginning, only the Supreme Court had power in the field of justice. Then developed with the formation of new institutions in the field of justice namely: the Constitutional Court and the Judicial Commission. Through these additions, it is expected that checks and balances will occur in the formation of laws and regulations and the implementation of judicial power.